Karakter Kemandirian dalam Novel Nyala Semesta Karya Farah Qoonita - Dewi, Juliana Candra; Wiza, Rahmi (MASALIQ, 2024)
It is very important for individuals to have independence so that they can live a good life because individuals who are not independent cannot optimize their potential. The character of emotional independence, behavior and values is important to grow within an individual in order to achieve a noble character. This research uses the content analysis method to obtain data on the character of independence in the novel Nyala Semesta by Farah Qoonita with the character Yusuf as the sample. The instrument in this research is a human instrument or the researcher himself. The data collection techniques used were coding sheets and literature study. The technique for analyzing data in this research is by filling in coding sheets according to the measurement tools that have been determined, carrying out validity tests, arranging the data in units of analysis so that they can be categorized and interpreting the data to draw conclusions from the research. It can be concluded in this research that in the novel Nyala Semesta by Farah Qoonita, it has been found and there really is a character of emotional independence, a character of behavioral independence and a character of value independence in it.